2017
DOI: 10.15761/jpr.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Hypogastric arteries ligation for the management of postpartum hemorrhage: a simple method of reducing uterine bleeding during surgery

Abstract: This prospective descriptive study, aimed at evaluating the efficacy of hypogastric arteries ligation (HAL) for the conservative surgical management of postpartum hemorrhage (PPH), as well as the maternal outcome, was conducted between April 1st 2010 and March 31 st 2014 in the University Teaching Hospital of Yaoundé (Cameroon). Sixteen women treated initially with HAL for PPH were recruited. The main variables recorded were maternal age and parity, the cause of PPH, the success of HAL, the additional surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(10 reference statements)
2
1
0
Order By: Relevance
“…In our study, out of forty-one patients, conservation of uterus was possible in thirty-six (87.8%) patients after satisfactory control of PPH. In a similar study, the rate of conservation of uterus was 75% as reported by Nkwabong et al 15 It was similar to our study result.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, out of forty-one patients, conservation of uterus was possible in thirty-six (87.8%) patients after satisfactory control of PPH. In a similar study, the rate of conservation of uterus was 75% as reported by Nkwabong et al 15 It was similar to our study result.…”
Section: Discussionsupporting
confidence: 93%
“…Nayak et al 4 reported the indications of IILA for uterine atony 46.6%, placenta praevia 13.3%, abruptio placenta 8.8%, rupture uterus 22.2%, lower genital tract injury 4.4% and broad ligament hematoma 4.4% respectively in their study subject. In another study, uterine atony was the most common indication for requiring IILA in the case series of PPH reported by Nkwabong et al 15 and Wankhede et al 17 Our study finding was similar to the study reported in the literatures.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation